Inventory of supply of articulated goods and services to promote the OVOP-Dota strategy, Costa Rica - Villalobos Moya, Keylor (2020)
In recent years, the OVOP movement has grown noticeably in Costa Rica due to the initiative of public sector institutions with the collaboration of international cooperation organizations. The purpose of these collaborations is to promote economic development and local identity through the generation and linking of community, entrepreneurial and business capacities based on the potential of local resources. The success of an OVOP strategy requires having systematized information on the supply of products and services available in the community as a basis for decision-making and for the management of community organization and local business processes. Since the County of Dota, one of the OVOP territories of Costa Rica, did not have information with the necessary degree of systematization, a diagnosis was made to characterize the enterprises in the main districts of the County. The information was collected through a primary source, specifically the application of surveys, telephone calls, and a secondary source (databases of the Municipality of Dota). The study was developed from 2018 to 2020. The results obtained showed that the largest number of enterprises are grouped in the food production category, followed by the categories of artisanal products and lodging. The analysis of the frequency of businesses by district determined that Santa María is the one with the highest concentration of ventures.